WRITING ANXIETY AND WRITING STRATEGIES USED BY ENGLISH DEPARTMENT STUDENTS OF UNIVERSITAS NEGERI PADANG - Masriani, Elsa; Mukhaiyar, Mukhaiyar; Wahyuni, Delvi (English Department FBS UNP, 2018)
This study investigated the levels and types of writing anxiety and writing strategies used by 3rd year English department students of Universitas Negeri Padang. The participants of this study were 41 students. This descriptive quantitative study used two questionnaires as the instrument. The first questionnaire was SLWAI (Second Language Writing Anxiety Inventory) by Cheng (2002) used to obtain the levels and types of writing anxiety. The writing strategies used by the participant were obtained from the second questionnaire namely Writing Strategy Scale developed by Raoofi et.al. (2017). The study found that the 3rdyear students of Universitas Negeri Padang experienced moderate level of writing anxiety with cognitive anxiety as the main type. The studey also found that the most used writing strategies were affective and metacognitive strategy.Key words/phrases: levels of writing anxiety, types of writing anxiety, writing strategiesÂ AbstrakArtikel ini bertujuan untuk menemukan level dan tipe kecemasan dalam menulis dan strategi menulis yang digunakan oleh mahasiswa tahun ketiga Jurusan Bahasa Inggris di Universitas Negeri Padang. 41 siswa dipilih sebagai responden dari penelitian ini. Penelitian ini merupakan penelitian deskriptif kuantitatif. Data didapakan dari membagikan 2 kuesioner. Kuesioner pertama yaitu SLWAI (Second Language Writing Anxiety Inventory) dari Cheng (2002) digunakan untuk mengetahui level dan tipe kecemasan responden. Kuisioner kedua yaitu Writing Strategy Scale dari Raoofi dkk (2017) digunakan untuk mengetahui strategi menulis yang digunakan responden. Penelitian ini menemukan bahwa responden mengalami kecemasan menulis dalam tingkat yang menengah, dengan tipe kognitif sebagai tipe yang mendominasi. Dari penelitian ini juga diketahui bahwa responden berada di level yang tinggi dalam penggunaan strategi menulis. Strategi yang sering digunakan yaitu strategi afektif dan metakognitif.Kata Kunci/frase: level kecemasan dalam menulis, tipe kecemasan dalam menulis, strategi menulis